(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
This paper investigates the raft houses of Palembang, known as "rumah rakit," which epitomize the affluent cultural amalgamation of Chinese and Malay influences. These floating dwellings, integral to the riverine lifestyle of Palembang, offer a unique lens through which to examine the historical and socio-cultural interactions between Chinese immigrants and the indigenous Malay community. The study employs comparative architectural analysis and historical documentation methods to uncover how these structures blend cultural practices, traditions, and environmental adaptations. The raft houses reflect the practical responses to living on water and symbolize the harmonious coexistence and mutual influence of Chinese and Malay cultures. By exploring these homes’ evolution, design, and cultural significance, the research highlights their role as living heritage sites that preserve and perpetuate the dynamic process of cross-cultural exchange. The findings underscore the importance of these structures in understanding the broader narrative of cultural integration and identity formation in Palembang, with the leader as a key factor in the “Rumah Rakit” transformation, especially in the stage of collective action to modify the raft house. That community’s collective action could be analyzed in another case of cross-cultural architecture.